Theorizing the Relationship between UK Schools and Immigrant Parents of Eastern and Central European Origin: the Parents’ Perspective - Christie, Sarah; Agnes , Agnes (International Journal about Parents in Education, 2023)
Schools may be particularly challenged in the building of relationships with immigrant families because of a potentially heightened mutual lack of knowledge or understanding about the other party’s cultural norms (e.g. Crozier & Davis, 2007). In the context of increased immigration from Eastern and Central European states, this study seeks to initiate the development of model of multi-cultural family-school interaction drawing on existing frameworks drawn from the fields of education, psychology and sociology. With the intention of establishing the nature of migrant parents’ constructions of their relationships with their children’s schools, we carried out in-depth, semi-structured interviews with 10 parents of school age children who had migrated to the UK from Eastern and Central Europe within the past 10 years. The key themes from the interviews indicated that the parents’ expectations of their children’s schooling appear to clash with those of the UK school system and that this is amplified by perceptions of poor communication, inadequate school-parent cooperation & marginalisation. Through the use of existing theoretical frameworks it was established that there is potential for improved practice though development of a model though this must take account of the full contextual complexity of the relationships.